Economics of Natural Gas Exports from Libya to Europe - Alkawfi, Mariam Mohamed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
In addition to being the holder of Africa’s largest proved crude oil reserves, Libya is a significant holder of natural gas reserves as well having the fifth largest proved reserves. Libyan proved reserves of natural gas are about 55 trillion cubic feet (tcf), although the period between 2004 and 2015 witnessed a dramatic increase in production of natural gas, the reserves remain stable during last decade. With reserves to production ratio above 100, Libya has the ability to produce gas not less than 100 years with output level of 10 bcm with potential to double this production Mac Donald M.( 2010) and Hanfer and Tagliapietra (2013). Libya has a significant potential to be a strategic supplier as compared to other natural gas suppliers to Europe in the Mediterranean region. In order to obtain a sustainable low-carbon economy, European Union countries are moving away from gasoline and diesel with high CO2 emissions towards efficient energy sources such as natural gas and renewable energy. The replacement of natural gas for coal and petroleum is reducing emissions of carbon (C2ES, 2013). In this study, we tested CO2 emissions convergence in EU countries and EKC in Italy. Also, we conducted a financial assessment of the natural gas pipeline project in Libya. Our findings refer to evidence of convergence in CO2 emissions, with absence of inverted U-shaped relationship in both EU countries and Italy. In addition, our financial analysis results show the capability for Libya to increase gas production and its potential to meet the demand in Europe by the developed natural gas pipeline. Keywords: Bahr Essalam, CBA, CO2 emissions, EKC, EU, natural gas pipeline, Libya , Italy.

ÖZ:Afrika’nın kanıtlanmış en büyük ham petrol rezervine sahip olmasının yanı sıra, Libya, kanıtlanmış en büyük beşinci doğal gaz rezervine sahiptir. Bu çalışma, doğal gaz boru hattı için fizibilite çalışması kullanarak Libya'nın doğal gaz piyasasında önemli bir rol oynama yeteneğini incelemeye çalışmaktadır. Libya’nın doğal gaz rezervlerinin yaklaşık 55 trilyon fit küp (tcf) olduğunu bilinmektedir. 2004 ve 2015 arasındaki dönemi, doğal gaz üretiminde çarpıcı bir artışa tanık olmasına rağmen, rezervler son on yılda sabit kalmıştır. 100'ün üzerindeki üretim oranına sahip rezervler ile Libya, Mac Donald M. (2010) ve Hanfer ve Tagliapietra (2013) göre bu üretimi ikiye katlama potansiyeli olan 10 bcm'lik üretim seviyesi ile 100 yıldan az olmamak üzere gaz üretme kabiliyetine sahiptir. Libya, Akdeniz bölgesindeki Avrupa'daki diğer doğal gaz tedarikçileri ile karşılaştırıldığında stratejik bir tedarikçi olma potansiyeline sahiptir. Sürdürülebilir düşük karbonlu bir ekonomi elde etmek için, Avrupa Birliği ülkeleri doğal gaz ve yenilenebilir enerji gibi verimli enerji kaynaklarına doğru yüksek CO2 emisyonlu benzin ve dizelden uzaklaşmaktadır. Kömür ve petrol için doğal gazın değiştirilmesi, karbon emisyonlarını azaltmaktadır (C2ES, 2013). Bu çalışmada, AB ülkelerinde CO2 salınımını ve İtalya'da EKC'yi test ettik. Ayrıca, Libya'daki doğal gaz boru hattı projesinin finansal bir değerlendirmesini yaptık. Bulgularımız, hem AB ülkelerinde hem de İtalya'da ters U şeklinde bir ilişki olmadığı için CO2 emisyonlarında yakınsama kanıtlarına işaret ediyor. Ek olarak, finansal analiz sonuçlarımız Libya'nın doğalgaz boru hattı ile doğalgaz üretimini artırma ve Avrupa'daki talebi karşılama potansiyelini göstermektedir. Anahtar Kelimeler: EKC, CBA, CO2 emisyonları, doğal gaz boru hattı, Bahr Essalam, Libya, AB, İtalya.
Doctor of Philosophy in Economics. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2019. Co-Supervisor: Prof. Dr. Glenn Paul Jenkins and Supervisor: Prof. Dr. Sevin Uğural.
Keywords: Natural gas-Economics-Libya; Natural gas-Economic aspects-Libya; Gas industry; Petroleum-resource economics; Energy Economics-Libya; Bahr Essalam; CBA; CO2 emissions; EKC; EU; natural gas pipeline; Libya; Italy